Possibilities of Block Play for the learning of Mathematics in Early Childhood Education - Castro Hernández, Carlos de; López Barrero, Desiré; Escorial González, Beatriz (Pulso. Revista de educación, 2011)
We present a mathematical, developmental, and educational guide to study block play in Early Childhood Education and to reflect on the possibilities that block play offers for the learning of mathematics. To this end, we describe a building material that promotes mathematical activity; we explain what kind of construction is performed by children from 2 to 6 years, and what development can be observed in block play in this age group. Then, we offer educational orientations to implement block play and to promote the learning of mathematics. We conclude by reflecting on sufficient conditions for block play to «ensure» that mathematical learning really takes place.
Keywords: Block Play; Early Childhood Education; Mathematics; Geometry; Measurement; Topology; Equivalence; Symmetry; Patterns